Concurrent papillary cancer of the thyroid gland and parathyroid carcinoma with paraplegia as the chief presenting complaint - Zakeri, Hamidreza; Rahmani, Fatemeh; Moussazadeh, Farhad; Samadian, Mohammad; Farahnaz, Falahati (European Journal of Oncology and Environmental Health, 2015)
Association of primary hyperparathyroidism with various malignancies is a known phenomenon. However, hyperparathyroidism presenting as a result of parathyroid carcinoma in association with Nonmedullary thyroid carcinoma is quite rare. In this report a rare case of primary hyperparathyroidism is presented in which paraplegia and radicular pain of lower limbs were the presenting symptoms. The patient was histopathologically diagnosed with concurrent papillary cancer of the thyroid gland and parathyroid carcinoma. The characteristics of the patient’s vertebral lesion were suggestive of Brown tumor. Ten days after parathyroidectomy, the patient exhibited delayed hungry bone syndrome.